Medulloblastoma in adults: treatment results and prognostic factors - (:unkn) unknown (My University, 2002)
PURPOSE: To investigate the treatment outcome and prognostic factors of adult medulloblastoma patients who received postoperative craniospinal irradiation (RT). METHODS AND MATERIALS: Between 1983 and 2000, 30 adult patients (17 men and 13 women, age >or=16 years, median 27, range 16-45) underwent postoperative RT. The median duration of symptoms was 2 months (range 1-9). The tumor location was lateral in 16 (53%). A desmoplastic variant was seen in 12 (40%). Tumor resection was complete in 20 (67%) and incomplete in 10 (33%). All patients received craniospinal RT. The median dose to the whole brain was 40 Gy (range 36-51), to the posterior fossa 54 Gy (range 49-56), and to the spinal axis 36 Gy (range 24-40). The median interval between surgery and the start of RT was 31 days (range 12-69), and the median duration of RT was 45 days (range 34-89). Ten patients (33%) received adjuvant chemotherapy. The median follow-up was 51 months (range 5-215). RESULTS: The 5- and 8-year overall survival and disease-free survival rates were 65% and 51% and 63% and 50%, respectively. Twelve patients (40%) developed relapse, with a median follow-up of 51 months. The posterior fossa was the most common site of relapse (6 patients). The median time to relapse was 26 months (range 4-78). Fifty percent of the relapses occurred after 2 years, 17% after 5 years. In univariate analysis, M stage and the interval between surgery and the start of RT were significant prognostic factors for disease-free survival. At 5 years, 70% of M0 patients were estimated to be disease-free, but none of the 3 M3 patients reached 5 years without recurrence (p = 0.0002). The 5-year disease-free survival rate for the patients whose interval between surgery and the start of RT was <3 weeks, between 3 and 6 weeks, and >6 weeks was 0%, 85%, and 75%, respectively (p = 0.002). The 5-year posterior fossa control rate for patients who received >or=54 Gy or <54 Gy to the posterior fossa was 91% and 33%, respectively (p = 0.05). CONCLUSION: The survival results for medulloblastomas in adults compare favorably with those in children. However, late relapses, lateral tumor location, and desmoplastic histologic features are more frequent in adults. Spinal seeding at presentation is a poor prognostic factor for disease-free survival. A minimal dose of 54 Gy to the posterior fossa is essential for adequate tumor control. The interval between surgery and the start of RT, which was found to be a significant prognostic factor, is an interesting issue that requires further study.
Keywords: Adult; Female; Humans; Middle Aged; Prognosis; Treatment Outcome; Adolescent; Male; Analysis of Variance; Recurrence; Spine; Cerebellar Neoplasms; Cranial Irradiation; Medulloblastoma; Postoperative Care; Radiotherapy Dosage